Examining Pancasila’s Position in the Public Reason Scheme: A Critical Analysis - Chaniago, Muhamad Iswardani (Jurnal Politik, 2019)
This research tries to review a number of ideas of some Indonesian scholars such as Yudi Latif, Franz Magnis-Suseno, and Syamsul Ma’arif, who saw and described the relationship between Pancasila and public reason, one of the popular political concepts in political studies. Some Indonesian scholars have linked Pancasila to public reason, with a secular nuance, so that it could potentially be free of religious associations. The troubled derivatives of public reason include (1) the negation of the principle of majoritarianism, (2) the neutral state principle, and (3) substantial elements in religion, such as the principle of universalism. With a qualitative study referring to a number of philosophical and historical arguments, it can be shown that the arguments given by the three aforementioned scholars, and others who share similar ideas, were considered to have a number of issues. From this review, it can be concluded that the thinking that supports the relationship between Pancasila and public reason is weak in terms of the secular argument. Therefore, the relation between Pancasila and public reason can be reviewed with more approachable ideas regarding religious contributions.